Discrimination of grape varieties by Start Codon targeted genotyping using partially degenerate primers - Miró, Krisztina; Nagy, Tibor; Korom, Edit; Marincs, Ferenc (Acta Biologica Szegediensis, 2017)
DNA fingerprinting of crop species should be technically simple and easy‑to‑perform, reproducible, and should provide sufficient amount of information. PCR‑based methods can meet one or more of these criteria, but they often employ multiple discrete primers or require to test large number of arbitrary primers to provide enough information, which make these methods technically complicated. Our aim was to develop a simple, reproducible, PCR‑based method for grape genotyping, which overcomes these limitations. We tested twelve, partly degenerate primers to genotype 14 Hungarian and international grape varieties and found one primer producing 17 polymorphic bands after data normalization, which was sufficient to separate the varieties. The discriminating power of this primer, in term of the number of polymorphic bands, PIC and Rp values, was the same or better than the SCoT primers with definite sequences described in previous studies. The phylogenetic tree obtained using sequences amplified with this primer was reliably consistent with the publicly available information about the genetic origin of some of the tested varieties. We developed a simple and accurate method to genotype grapevine, which provided sufficient amount of data to discriminate 14 varieties.